The Effectiveness of Using English Songs in Improving the Vocabulary of Eighth-Grade Students of MTs Nurul-Qur’an Patokan - Wildatuzzahrany Wildatuzzahrany; Mery Silalahi; Widya Syafitri (CV Wahana Publikasi, 2026)
This study evaluates the effectiveness of using English songs in developing the vocabulary mastery of eighth-grade students at MTs Nurul-Qur’an Patokan. The underlying problem motivating this research is students’ limited interest in and comprehension of English vocabulary, which constitutes a significant obstacle to learning. A quantitative method with a quasi-experimental pre-test-post-test control group design was adopted. The study population comprised all Grade VIII students, from which two classes were selected as samples: one as the experimental group, which received instruction through English songs, and one as the control group, which continued with conventional learning methods. Data were collected through pre-tests and post-tests and analyzed using an independent samples t-test. The results demonstrated that the use of English songs had a significant positive effect on the vocabulary mastery of students in the experimental group compared to the control group, with average scores rising from 58.3 to 82.6 in the experimental group versus 57.5 to 68.2 in the control group (p-value = 0.003). These findings indicate that the use of English songs is not only statistically effective but also has strong practical value in classroom instruction, as it can meaningfully enhance students’ vocabulary mastery while increasing engagement and motivation in learning English. Therefore, integrating songs into vocabulary teaching is recommended as an enjoyable, interactive, and pedagogically beneficial strategy that can be applied consistently to improve learning outcomes in junior high school settings.